A System Approach to Implementing Business Ethics in the Corporate Workplace - Clarke , Clifton (Journal of Law and Governance, 2011)
The current vitriolic discourse over the financial scandals implicating Wall Street and its satellite institutions dictates a fresh look at strategies intended to eradicate or prevent unethical practices in business activities. The spate of recently published unethical behavior among business executives in the United States confirms, unequivocally, that past and current strategies have failed. This paper reviews and evaluates the impact of some of these strategies. It found that the strategies focus on legislation, written corporate codes of ethics and assorted activities in business schools. It found that these strategies are largely isolated and missed the fact that unethical business conduct is systemic, reflecting the ethical lapses of two systems: a public system (consisting of governmental bodies, business schools, and the general citizenry) and a corporate system (consisting of boards of directors, executives, managers and employees). It found that there is a significant gap between the rhetoric of corporate executives and their attention to unethical conduct in the workplace. It concludes that isolated legislative actions, apathetic business schools’ policies, complacent and complicit corporate boards, contribute to the failure. It also concludes that, the implementation of business ethics in the workplace requires a transformation of attitude within and between these systems and posits that a system approach is the only strategy that can successfully transform these systems and that business schools are uniquely capable of leading this transformation.